Urban growth or development - Villergas Ormachea, Americo (2015)
The article discusses the problem of generic urban  process; conceptual decomposition and practices in the development and urban expansion in the inhabited areas of southern Peru macro. The construccion process of urban space in times of economic growth and sub parallel development: imposible projection of a sustainable habitat.